An Activatable Hybrid Organic–Inorganic Nanocomposite as Early Evaluation System of Therapy Effect. (27th December 2021) - Fu, Qinrui; Feng, Hongjuan; Su, Lichao; Zhang, Xuan; Liu, Luntao; Fu, Fengfu; Yang, Huanghao; Song, Jibin
Abstract: Delays in evaluating cancer response to radiotherapy (RT) usually reduce therapy effect or miss the right time for treatment optimization. Hence, exploring timely and accurate methods enabling one to gain insights of RT response are highly desirable. In this study, we have developed an apoptosis enzyme (caspase‐3) activated nanoprobe for early evaluation of RT efficacy. The nanoprobe bridged the nanogapped gold nanoparticles (AuNNPs) and the second near‐infrared window (NIR‐II) fluorescent (FL) molecules (IR‐1048) through a caspase‐3 specific peptide sequence (DEVD) (AuNNP@DEVD‐IR1048). After X‐ray irradiation, caspase‐3 was activated to cut DEVD, turning on both NIR‐II FL and PA imaging signals. The increased NIR‐II FL/PA signals exhibited a positive correlation with the content of caspase‐3. Moreover, the amount of the activated caspase‐3 was negatively correlated with the tumor size. The results underscore the role of the caspase‐3 activated by X‐ray irradiation in bridging the imaging signals variation and tumor inhibition rate. Overall, activatable NIR‐II FL/PA imaging was successfully used to timely predict and evaluate the RT efficacy. The evaluation system based on biomarker‐triggered living imaging has the capacity to guide treatment decisions for numerous cancer types. Abstract : In vivo "Turn‐On" NIR‐II FL and NIR‐II PA signals by using activated caspases‐3 after radiotherapy to proteolytically cleave the peptide sequence of an AuNNP@DEVD‐IR1048 nanoprobe, in addition to integrating living imaging information with a radiotherapy effect using the caspase‐3 enzyme as "matchmaker" and developing the relationship between each other, enable real‐time evaluation and early prediction of radiotherapy effects.